1991
DOI: 10.1007/bf02990421
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution and urinary excretion of essential elements in rats orally exposed to aluminum chloride

Abstract: The purpose of this study was to determine disorders in the metabolism of the essential elements (Ca, Fe, Cu, and Zn) in some tissues of rats, as well as to detect the dynamics of urinary excretion of these metals after oral administration of 20 mgAl/kg every day for 8 wk. The elements were determined in brain, kidneys, blood, and urine of the animals in 1st, 2nd, 3rd, 4th, and 8th wk after the exposure to AlCl3. After the 1st wk of aluminium administration, we observed increase of Ca and a decrease of Fe in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…A number of studies have shown that animals exposed to AlCl 3 have increased Al concentrations in liver, plasma, urinary, kidney [14], testis and serum [15], hippocampus [16], and brain [17,18]. In the present study, there has been a significant increase in liver Al level after AlCl 3 exposure.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A number of studies have shown that animals exposed to AlCl 3 have increased Al concentrations in liver, plasma, urinary, kidney [14], testis and serum [15], hippocampus [16], and brain [17,18]. In the present study, there has been a significant increase in liver Al level after AlCl 3 exposure.…”
Section: Discussionsupporting
confidence: 60%
“…It was observed that Fe level in liver of AlCl 3 administered group was found to be increased compared to the control group. Some studies have shown that animals that are exposed to Al have had increased Fe concentrations in brain, urinary excretion [17] and testis [15]. Ward RJ et al noted that in an animal model of Al overload, increases in tissue iron in kidney, liver, heart and spleen, and also in various brain regions, such as frontal, temporal and parietal cortex and hippocampus, has been parallel to the increase at tissue A1 content [21] .…”
Section: Discussionmentioning
confidence: 99%
“…This effect also implicates the Al accumulated in small intestine, and also the probable reduction in the renal production of 1,25-(OH) 2 -D 3 . A disorder in the metabolism of Ca, with an increase in its excretion, has been observed in animals treated with aluminum via an oral route (Chmielnicka and Nasiadek 1991). Nevertheless, data showing that the oral administration of aluminum produces a diminution in calcium excretion have been reported (Sanchez et al 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Calcium concentrations (pg/g weight of tissue) in tissues of young, adult and old rats exposed to 0, 50, or 100 mg AVkg/day for a period of 6.5 months. mation on the interaction of A1 with essential elements is rather scarce (Greger & Baier 1983;Greger et al 1985Greger et al & 1986Chmielnicka & Nasiadek 1991;Muller et al 1993;Liu & Nordberg 1995). Particularly scarce is the information on the effects of both A1 and aging on the mineral status in mammals.…”
mentioning
confidence: 99%
“…1985;Blanusa et al 1989;Liu et al 1991). Thus, while the interaction of lead with iron, zinc and copper was mainly attributable to competition in absorption at the intestinal level (Blanusa et al 1989), parenteral A1 was suggested to interact with the gastrointestinal calcium transportary system and to affect iron distribution and metabolism (Chmielnicka & Nasiadek 1991). On the other hand, significant alterations in mineral status with age were also observed (Morita et al 1994).…”
mentioning
confidence: 99%